Measuring retinal contributions to the optical Stiles-Crawford effect with optical coherence tomography - Gao, Weihua (2008)
The directional component of the retinal reflection, i.e., the optical Stiles-Crawford effect (SCE), is well established to result from the waveguiding property of photoreceptors. Considerable uncertainty, however, remains as to which retinal reflections are waveguided and thus contribute. To this end we have developed a retina camera based on spectral-domain optical coherence tomography (SD-OCT) that axially resolves (~5 μm) these reflections and permits a direct investigation of the SCE origin at near infrared wavelengths. Reflections from the photoreceptor inner/outer segments junction (IS/OS) and near the posterior tip of the outer segments (PTOS) were found highly sensitive to beam entry position in the pupil with a considerable decrease in brightness occurring with an increase in aperture eccentricity. Reflections from the retinal pigment epithelium (RPE) were largely insensitive. The average directionality (ρ(oct) value) at 2 degree eccentricity across the four subjects for the IS/OS, PTOS, and RPE were 0.120, 0.270, and 0.016 mm(−2), respectively. The directionality for the IS/OS approached typical psychophysical SCE measurements, while that for the PTOS approached conventional optical SCE measurements. Precise measurement of the optical SCE was found to require significant A-scan averaging.